2010
DOI: 10.1590/s1516-31802010000300006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and metabolic syndrome risk among men with and without erectile dysfunction: case-control study

Abstract: CONTEXT AND OBJECTIVE: Erectile dysfunction has been associated with cardiovascular diseases. The aim here was to evaluate cardiovascular risk through the Framingham Risk Score (FRS) criteria, C-reactive protein (CRP) assays and presence of metabolic syndrome (MS) in men with and without erectile dysfunction diagnosed within a healthcare program. DESIGN AND SETTING: A retrospective case-control study was conducted. The patients were selected from a healthcare program at the Hospital Israelita Albert Einstein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
1
21
1
6
Order By: Relevance
“…Patients with higher body mass index are at greater risk of ED, even at the prospect of weight loss. Clinical factors like waist-hip ratio, body mass index and resting heart rate are significantly higher in patients with ED (Muller & Mulhall, 2006;Zambon, 2010).…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 94%
See 3 more Smart Citations
“…Patients with higher body mass index are at greater risk of ED, even at the prospect of weight loss. Clinical factors like waist-hip ratio, body mass index and resting heart rate are significantly higher in patients with ED (Muller & Mulhall, 2006;Zambon, 2010).…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 94%
“…Besides, hypercholesterolemia increases the proinflammatory markers and endothelial dysfunction. (Vrentzos, 2007;Bal, 2007) Studies demonstrated a positive correlation between cardiovascular risks, hypercholesterolemia and erectile dysfunction (Zambon, 2010;Koenig, 2004) have demonstrated that men with ED had higher levels of C-reactive protein, which is an early marker of endothelial dysfunction and cardiovascular diseases. (Zambon, 2010;Koenig, 2004) …”
Section: Dyslipidemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Homens com histórico de câncer de próstata, hipertensão arterial, tabagismo, obesidade, diabetes e depressão, também têm risco aumentado para DE 3,4 . Ainda, homens com DE grave apresentam maior risco de ter síndrome metabólica 5 . No Brasil, um estudo realizado em homens com média de idade de 37,6 anos, constatou que 45,1% apresentaram algum nível de DE, sendo 31,2% mí-nima, 12,2% moderada e 1,7% completa 3 .…”
Section: Introductionunclassified